FAKTOR-FAKTOR YANG MEMENGARUHI PENDAPATAN INDUSTRI BAWANG GORENG DI KOTA PALU - Shintami Rouwelvia Malik; Made Antara; Sulaeman Sulaeman (Universitas Tadulako, 2017)
The purpose of this research were to identify and analyze factors influencing the income of fried onion industry perceived from the aspects of its price, production cost, advertising cost, the amount of raw materials used and the number of labor used, and to determine the level of fried onion industry income in Palu. Respondents were selected using a purposive sampling technique with which 32 fried onion industries with production capacity ranging from 3000 – 18,000 kg year-1 were chosen.The results of analysis showed that the factors including the price (X1), the production cost (X2), the advertising cost (X3), the amount of raw materials (X4) and the number of labor (X5) simultaneously had highly significant effect on the income of the fried onion indicated by F-test (1435,106) >F-table (3.82) for the 99% significant level. Therefore, H0 was rejected and H1 accepted. The results of t-test indicated that except the number of labor (X5), the other factors such as the price (X1), the production cost (X2), the advertising cost (X3), the amount of raw materials (X4) and the number of labor (X5)partially had significant affect on the income of the fried onion industry.. The results of revenue and income analyses showed that the production was 582.81 kg month-1 of fried onion in average with the average revenue of IDR 130.586.425,78, and the average income of IDR 76.128.503,19 industry-1month Key words: Fried onion, Income, Regression analysis.